CPAP and Health-Related Quality of Life in Adults With Coronary Artery Disease and Nonsleepy Obstructive Sleep Apnea in the RICCADSA Trial - BALCAN, MEHMET BARAN (AMER ACAD SLEEP MEDICINE, 2019)
Study Objectives: To determine the effect of continuous positive airway pressure (CPAP) treatment on health-related quality of life (HRQoL) in adults with coronary artery disease (CAD) and nonsleepy obstructive sleep apnea (OSA). Methods: This was a secondary outcome analysis of the RICCADSA trial, conducted in Sweden between 2005 and 2013. Adults with CAD, nonsleepy OSA (apnea-hypopnea index [AHI] >= 15 events/h; Epworth Sleepiness Scale [ESS] score < 10) and complete Short-Form (SF)-36 questionnaires at baseline and after 12 months were included. Patients were randomized to CPAP (n = 102) or no CPAP (n = 104). The primary outcome was the between-group difference in absolute change in the SF-36 components. Within-group changes as well as variables associated with absolute change in the domains in the entire population were also tested. Results: Mean SF-36 scores were similar at baseline, ranging from 44.9 +/- 9.6 to 92.2 +/- 15.8 in various domains, and between-group changes from baseline were not statistically significant at 1 year. There was a significant increase in Role physical, Vitality, Role emotional, Mental health and Mental Component Summary (MCS), and a decrease in Bodily pain and General health scores in the CPAP group. The change in Physical Component Summary (PCS) was determined by female sex (beta coefficient -0.19, 95% confidence interval [CI] -7.25 to -0.98, P = .010), baseline AHI (beta coefficient -0.19, 95% CI -0.21 to -0.03, P = .009), CPAP use (h/night) (beta coefficient -0.16, 95% CI -0.93 to -0.06, P = .028), and acute myocardial infarction at baseline (beta coefficient 0.18, 95% CI 0.59 to 5.19, P = .014). Determinants of the change in MCS from baseline were change in the ESS score (beta coefficient -0.14, 95% CI -0.87 to -0.01, P =.054) and change in the Zung Self-rated Depression Scale scores (beta coefficient -0.33, 95% CI -0.58 to -0.24, P < .001). Conclusions: Assignment to CPAP treatment compared to no CPAP had no significant effect on HRQoL as measured by the SF-36 in adults with CAD and nonsleepy OSA. Although several components of the SF-36 scores were improved within the CPAP group, CPAP use was associated with a decrease in PCS. The improvement in MCS was determined by the improvement in daytime sleepiness and depressive mood.
Keywords: cardiovascular disease; health-related quality of life; SF-36; sleep apnea; POSITIVE AIRWAY PRESSURE; CARDIOVASCULAR OUTCOMES; DAYTIME SLEEPINESS; HEART; ASSOCIATION; PREDICTORS; SYMPTOMS; THERAPY; IMPACT; RISK